Network Governance Dalam Pemenuhan Ketersediaan Pangan Di Kota Malang - Yana Syafrieyana Hijri; Muhammad Kamil; Bayu Sadewo; Iradhad Taqwa Sihidi (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2021)
This study describes the policy response to the conversion of agricultural land in Malang City from the perspective of Network Governance which was coined by Keith G. Provan. This departs from the fact that in five years there has been a quite massive conversion of agricultural land in Malang City so that which threatens food availability. The collaboration pictured involves the Department of Agriculture and Food Security, the Department of Trade, and the Malang Subdivre Bulog Public Corporation. The research method used in this research is descriptive qualitative. The research resulted in the findings that the implementation of inter-agency network governance has been carried out well through the main program, namely market operations which are intended to provide access to food to the public at a standard price. However, there are several obstacles in carrying out the network management, including the quality of rice distributed and Malang City which does not have City Government Rice Reserves.